Enhanced non-linear current-voltage response of Te-doped calcium copper titanate ceramics. Issue 8 (1st June 2017) - Barman, Nabadyuti; Varma, K.B.R.
Abstract: The influence of partial replacement of Ti 4+ ions by Te 4+ in calcium copper titanate lattice on dielectric and non-linear current- voltage (I–V) characteristics was systematically studied. There was a remarkable increase in the values of the nonlinear coefficient (α) with Te 4+ doping concentration in CaCu3 Ti4- x Te x O12 (where, x =0, 0.1, 0.2).For instance, the α values increase from 2.9 ( x =0) to 22.7 ( x =0.2) for ceramics sintered at 1323 K/8 h. The room temperature value of current density (J) at the electrical field of 250 V/cm for CaCu3 Ti3.8 Te0.2 O12 ceramics is almost 400 times higher than that of the pure CaCu3 Ti4 O12 ceramics sintered at 1323 K. A systematic investigation into I–V behaviour as a function of temperature gave an insight into the conduction mechanisms of undoped and doped ceramics of calcium copper titanate (CCTO). The calculated potential barrier value for doped ceramics ( 0.21 eV) dropped down to almost one third that of the undoped ceramics ( 0.63 eV).